Analysis of the radioprotective properties of 3-hydroxypyridine fumarate on an invertebrate animal model after proton irradiation in vivo - O. V. Kuzmicheva; D. V. Uskalova; D. T. Degtyareva; T. V. Ulanova; S. V. Shkavrov; E. I. Sarapultseva (Радиационная гигиена)
The purpose of the article is to analyze the radio protective and antioxidant properties of 3-hydroxypyridine fumarate in interaction with proton irradiation on a model test organism from the suborder Daphnia magna crustaceans in vivo.   The salt of 3-hydroxypyridine fumarate synthesized by the authors was a white crystalline substance soluble in alcohol and water – a mixture of 2-ethyl-6-methyl-3-hydroxypyridine and fumaric acid in ethanol. Acute irradiation of the test organism was carried out on the Prometheus proton complex at the А. Tsyb Medical Radiological Research Center (Obninsk, Russia) with a scanning proton beam at a dose of 30 Gy (energy 150 MeV) in a distributed Bragg peak. The survival rate of D. magna was assessed in a 21-day experiment on a daily basis. The cytotoxicity of the studied factors was analyzed by changes in MTT and MDA parameters, the antioxidant properties of 3-hydroxypyridine fumarate were evaluated by changes in the activity of catalase, peroxidase and superoxide dismutase enzymes. The contribution of the analyzed factors to the observed effects was assessed using the Kruskal-Wallis test. Statistical processing of survival was carried out according to the χ2 criterion, and other indicators – according to the Mann-Whitney criterion, adjusted for multiple comparisons. According to the data obtained, the survival rate of irradiated newborn animals decreased by 29.3 % by the age of 21 days (p = 0.03). When combined with 3-hydroxypyridine fumarate action, the death of animals decreased to 44.4 % (p = 8.8 x 104). It was revealed that radiation contributed to the joint effect. An integral assessment of the level of oxidative stress showed that proton irradiation causes a cytotoxic effect in the cells of the test organism. 3-hydroxypyridine fumarate does not have radioprotective and antioxidant effects when D. magna is cultured in a solution of a substance with a concentration of 0.05 micrograms/ml after proton irradiation. The results obtained are consistent with the data on the absence of radioprotective properties of 3-hydroxypyridine fumarate after irradiation with heavy ions. The authors propose a unified mechanism of interaction between 3-hydroxypyridine fumarate and densely ionizing radiation of various types (protons, heavy ions, alpha particles), which does not exhibit radioprotective effects. It is necessary to continue the search for radioprotectors for proton therapy among substances of a different class.